Comparative Study of Conventional (Cast-In Situ) & Pre-Cast Method for Residential Project: A comprehensive analysis of conventional and pre-cast construction methods in the residential project development in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Based on recent scenario, India has begun towards industrialization in all features of development. Construction industry in now days became a Fast, Developed, Modernized, Time Effective, Cost Efficient and Adopting Advance Construction Techniques. The Objective of study is to find the Present situation of the Pre-cast Construction Technique in India, Finding the Feasibility Study of Conventional (Cast In-situ) Vs. Pre-Cast Construction Method. This study focuses on different concepts of Pre-cast Construction Technique. A literature survey done highlights the facts associated with it. This study compares the parameters or area of effectiveness of both the Conventional and Pre-cast Technique.